How Should Home-Based Maternal and Child Health Records Be Implemented? A Global Framework Analysis - Mahadevan, Sruthi; Broaddus-Shea, Elena T. (Global health science and practice, 2020)
A home-based record (HBR) is a health document kept by the patient or their caregivers, rather than by the health care facility. HBRs are used in 163 countries, but they have not been implemented universally or consistently. Effective implementation maximizes both health impacts and cost-effectiveness. We sought to examine this research-to-practice gap and delineate the facilitators and barriers to the effective implementation and use of maternal and child health HBRs especially in low- and middle-income countries (LMICs). Using a framework analysis approach, we created a framework of implementation categories in advance using subject expert inputs. We collected information through 2 streams. First, we screened 69 gray literature documents, of which 18 were included for analysis. Second, we conducted semi-structured interviews with 12 key informants, each of whom had extensive experience with HBR implementation. We abstracted the relevant data from the documents and interviews into an analytic matrix. The matrix was based on the initial framework and adjusted according to emergent categories from the data. We identified 8 contributors to successful HBR implementation. These include establishing high-level support from the government and ensuring clear communication between all ministries and nongovernmental organizations involved. Choice of appropriate contents within the record was noted as important for alignment with the health system and for end user acceptance, as were the design, its physical durability, and timely redesigns. Logistical considerations, such as covering costs sustainably and arranging printing and distribution, could be potential bottlenecks. Finally, end users' engagement with HBRs depended on how the record was initially introduced to them and how its importance was reinforced over time by those in leadership positions. This framework analysis is the first study to take a more comprehensive and broad approach to the HBR implementation process in LMICs. The findings provide guidance for policy makers, donors, and health care practitioners regarding best implementation practice and effective HBR use, as well as where further research is required.